Sarcasm Types in Meghan Trainor’s Song Entitled “Mother” - Sari, Wati Purnama (Jurnal Ilmiah Multidisiplin, 2023)
The research aim is to figure out types of sarcasm used in Meghan Trainor’s song entitled “Mother”. The descriptive qualitative method is used in this research. In analyzing the data, the researcher used theory of sarcasm types advocated by Elisabeth Camp. The results of research showed that there are two types of sarcasm used in Meghan Trainor’s song entitled “Mother” namely, the illocutionary sarcasm (3 data found) and the lexical sarcasm (13 data found). The lexical sarcasm is the most used sarcasm type in the Meghan Trainor’s song entitled “Mother”. The lexical sarcasm used in that song indicates that the songwriter wanted to deliver her critics with vivid, strong and explicit messages to the audiences.